Composition in the Ensemble Classroom: Ideas From Eight Researcher-Designed Methods. (October 2019) - Taft, Seth A.
Composition is a natural human activity that can both support other music instruction and help students develop creativity that is applicable to their extramusical endeavors. It also constitutes a major strand within national and state music standards. However, it is not consistently taught in ensemble classrooms, which are often students' only form of music education past elementary school. In this article, I briefly summarize arguments in favor of composition instruction, then describe and analyze eight composition units and activities developed by researchers for use in the ensemble classroom. I conclude the article with a synthesis of the implications of the methods, along with other research on composition, into eight key ideas to help ensemble directors implement composition instruction in their classrooms. This article serves as a starting point for ensemble directors hoping to implement composition while also directing them to several other resources they might use.